The relationship between perceived loneliness and depression in the elderly and influencing factors. Issue 1 (5th July 2020) - Isik, Kevser; Başoğul, Ceyda; Yildirim, Hilal
Abstract: Purpose: This study was carried out to determine the relationship between perceived loneliness and depression in the elderly and influencing factors Design and Methods: This cross‐sectional descriptive study was conducted with 501 elderly. Data were collected with the questionnaire form, the elderly loneliness scale and the geriatric depression scale. Findings: A positive relationship was found between depression and loneliness. Loneliness, applying to a family health center/hospitalization, educational level, social loneliness, and age were found to be the predictors of depression. Depression, applying to a family health center/hospitalization, and marital status were found to be the predictors of loneliness. Practical Implications: Loneliness is the major factor affecting depression in elderly. It is recommended that attempts should be made to enable the elderly to live more actively.